2015
DOI: 10.3389/fmicb.2014.00740
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal cryptococcosis from 1977 to 2013

Abstract: Skeletal cryptococcosis, an aspect of disseminated cryptococcal disease or isolated skeletal cryptococcal infection, is a rare but treatable disease. However, limited information is available regarding its clinical features, treatment, and prognosis. This systematic review examined all cases published between April 1977 and May 2013 with regard to the factors associated with this disease, including patient sex, age, and epidemiological history; affected sites; clinical symptoms; underlying diseases; laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 95 publications
1
54
1
1
Order By: Relevance
“…Most patients present with a soft exophytic mass, as in our case. The most common source of cryptococcal osteomyelitis is hematogenous dissemination from a primary site such as the lung . However, in our case, no other primary site of infection was found, leading to the conclusion that the original trauma and skin lesion were a portal for direct inoculation of C. neoformans .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Most patients present with a soft exophytic mass, as in our case. The most common source of cryptococcal osteomyelitis is hematogenous dissemination from a primary site such as the lung . However, in our case, no other primary site of infection was found, leading to the conclusion that the original trauma and skin lesion were a portal for direct inoculation of C. neoformans .…”
Section: Discussionmentioning
confidence: 48%
“…Although the optimal duration of antifungal therapy for SOT recipients with isolated cryptococcal osteomyelitis has not been studied, the Infectious Diseases Society of America (IDSA) guidelines recommend 6–12 months of therapy for moderate‐to‐severe non‐CNS or disseminated disease . Antifungals alone or in conjunction with surgery have demonstrated efficacy . Intravenous AmB with flucytosine is typically used for CNS or disseminated cryptococcal disease in the initial stages; however, one report describes successful use of an oral regimen of fluconazole and 5‐flucytosine in a liver transplant patient who developed renal impairment with AmB .…”
Section: Discussionmentioning
confidence: 99%
“…In each of our five patients, symptoms and findings associated with osseous involvement were the first signs of cryptococcosis, and the pursuit of these findings ultimately led to the diagnosis. Prior authors have reported the most common site of infection was the vertebral column, seen in a quarter to one‐third of patients . In our review, 12 of 42 (29%) had vertebral infection.…”
Section: Literature Review and Discussionmentioning
confidence: 58%
“…Bony involvement due to Cryptococcus species is uncommon, with an estimated prevalence of 5% and is usually seen in association with multi‐organ disseminated disease. Isolated cryptococcal osteomyelitis as the sole manifestation of extra‐pulmonary disease is a rare event, and occurs as a result of haematogenous dissemination following primary pulmonary infection …”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…es poco común, con una prevalencia estimada de 5-10% 2 en el contexto de una infección diseminada. La osteomielitis criptocóccica aislada como la única manifestación de la enfermedad extrapulmonar y fuera del SNC es muy infrecuente y ocurre como resultado de una diseminación hematógena después de una infección pulmonar primaria 2,9 . Otras fuentes potenciales son los traumatismos óseos, embolias sépticas, o la infección de la piel o neural contigua 10 .…”
Section: Discussionunclassified